FEA of Effects Induced by Diurnal Temperature Variation on Downstream Surface of Xiaowan Arch Dam. (30th June 2021) - Li, Huanhuan; Fu, Shaojun; Li, Gang; Hu, Guofei
Abstract : In order to make clear the cracking reasons in arch dam of Xiaowan Hydropower Station during operation period, the approach to combine ANSYS with finite element program COCE-3D is adopted. Firstly, the influence by element type and mesh size for the temperature field simulation result is analyzed. Subsequently, the three typical dam segments cut from Xiaowan arch dam are selected and the relevant finite element model is established; the effect of the measured diurnal air temperature on temperature field and temperature stress of arch dam is analyzed thoroughly. The results indicate that the temperature gradient in mass concrete becomes lower, whereas the affecting depth becomes deeper when the mesh size is too large. Therefore, it is advisable to use smaller size mesh to study the influence of the measured diurnal air temperature on the surface temperature distribution in mass concrete. The temperature of downstream zone in arch dam is significantly affected by air temperature; the changing laws of temperature field and temperature stress with the air temperature are basically consistent, which is sensitive to lower temperature. When the temperature sharply decreased, the temperature stress in the downstream zone is mainly in tensile stress state. The calculated results are basically consistent with the measured results, and the temperature stress induced by the day-night temperature difference is the important reason for the horizontal cracks on the downstream surface. The submodel analysis method is an important alternative approach to study the changing laws of temperature field of arch dam. The research results not only provide an evidence for temperature control and crack prevention of Xiaowan arch dam but also provide a reference for temperature field simulation of similar projects.